Travessia e impasse: O lugar de Sebastião Uchoa Leite na poesia contemporânea - Andrade, Paulo [UNESP] (My University, 2005)
Sebastião Uchoa Leite's work is circumscribed in a field of tension with tradition, which makes impossible is delimitation to anyone who seeks to draw his poetic profile. The undeniable identification with the modernist masters does not mean the enhancement of such standards; on the contrary, they are contaminated by the crossing of the most diverse references. The ambiguity comes from the fact that the poet neither puts limits in a temporal-spaced territory, nor sets defined directions. His is a hybrid textual project, as in a crossing, which the nomad route places, side by side, the referring speeches from tradition and from the contemporary world.

A obra de Sebastião Uchoa Leite é circunscrita num campo de tensão desvio e aproximação com a tradição, o que impossibilita a demarcação de limites a quem busca traçar um contorno da sua poética. A inegável identificação com os mestres modernistas não significa a ampliação de tais modelos, ao contrário, estes são contaminados pelo entrecruzamento de referências as mais diversas. A indecidível ambigüidade decorre do fato de que o peta não demarca nenhum território espaço-temporal, nem norteia direções definidas. Trata-se de um projeto textual híbrido, de travessia, cujo percurso nômade faz transitar, lado a lado, discursos referenciais da tradição e do mundo contemporâneo.
Crossing and dilemma: The modernist tradition in Sebastião Uchoa Leite's poetry
Keywords: Aesthetic modernity; Contemporary poetry; Sebastião Uchoa Leite